Examining the Absorbency and Elasticity Properties of Modified Coconut Fibre: An Alternative Material for Diapers Filling - Kusumawati, Intan; Marwoto, Putut; Rusilowati, Ani; Sumarni, Woro; Priatmoko, Sigit (STKIP Singkawang, 2025)
Research on absorbent core and elastic-modified coconut fibre is motivated by the use of coconut fibre in terms of water absorption and elasticity. This study aims to: (1) determine the percentage of the absorbent core and elastic-modified coconut coir; (2) compare the percentage of the absorbent core and elastic-modified coconut fibre to the diapers X. The design used was experimental. The tools and materials consisted of modified coconut fibre, a Pasteur pipette, a specimen clamp, and a software system. Modified coconut coir was made from a mixture of Cinnamomum verum and Mutingia calabura L., with a sample mass ratio to diapers X, which was 1:40, circular shape with a diameter of 3 cm. The treatments for modified coconut coir were sun drying (Sample A) and a hair dryer (Sample B), which resulted in differences in the Absorbent core (Ab) and Elastic (E). The sample was forwarded for the E-test through the Tracker software system, which can detect the centre of mass of the object through the experimental video recording, and the other sample was measured Ab through the difference in the volume of water absorption. The results showed that Sample B could be used as an engineering material for Ab and E diapers X. It was concluded that: (1) %Ab-Sample B = 38.36%, %Ab-Sample A = 25.57%, %E-Sample B = 1.2%, %E-Sample A = 0.5%; (2) comparison of %E-Sample B to %E-Diapers X was 67%, and %E-Sample A to %E-Diapers X was 27%.